Bentuk Adaptasi Lingkungan Pada Permukiman Tradisional di Danau Toba - Taufiqurrahman Setiawan (Berkala Arkeologi Sangkhakala, 2010)
AbstractBatak traditional settlements around Toba Lake have pattern and specific forms. Those are very influenced by some supporting factors, ie. environment factors, landform, potential resources and accessibility. There are also important elements that must be exist within.That elements a result of the adaptation process of Batak Toba communities to their environment.